The impact of dehydration and extremely low HCl values in the Antarctic stratospheric vortex in mid-winter on ozone loss in spring - Zhang-Liu, Yiran; Müller, Rolf; Grooß, Jens-Uwe; Robrecht, Sabine; Vogel, Bärbel; Zafar, Abdul Mannan; Lehmann, Ralph (Copernicus Publications, 2024)
Simulations of Antarctic chlorine and ozone chemistry show that in the core of the Antarctic vortex (16–18 km, 85–55 hPa, 390–430 K) HCl null cycles (initiated by reactions CH4 + Cl and CH2O + Cl) are effective. These HCl null cycles allow HCl mixing ratios to remain very low throughout Antarctic winter and ozone destroying chlorine (ClOx) to remain enhanced, so that rapid ozone depletion proceeds. Sensitivity studies show that the reaction CH3O2 + ClO is important for the efficacy of the HCl null cycle initiated by the reaction CH4 + Cl and that using the current kinetic recommendations instead of earlier ones has little impact on the simulations. Dehydration in Antarctica strongly reduces ice formation and the uptake of HNO3 from the gas phase; however the efficacy of HCl null cycles is not affected. Further, the effect of the observed very low HCl mixing ratios in Antarctic winter are considered; HCl null cycles are efficient in maintaining low HCl (and high ClOx) throughout Antarctic winter. All simulations presented here for the core of the Antarctic vortex show extremely low minimum ozone values (below 50 ppb) in late September/early October in agreement with observations.